Comparison of dosimetric parameters between intensity modulated and three-dimensional conformal radiotherapy planning for adjuvant therapy of gastric cancer - Sharmin, Sadia; Mollah, M. Nazir Uddin; Ruma, Rokaya Sultana; Rasheed, M. Mamoon O.; Anika, Afsana Sharmin; Haque , M. Saidul (International Journal of Research in Medical Sciences, 2023)
Background: Adjuvant chemoradiotherapy is the standard treatment for gastric carcinoma, but the optimal radiation modality remains uncertain. This study aimed to compare intensity-modulated radiotherapy (IMRT) and three-dimensional conformal radiotherapy (3D-CRT) in terms of dosimetry for adjuvant gastric cancer treatment. Methods: 21 patients with stage IIB-IIIC gastric cancer, treated between January and June 2021, underwent surgery followed by adjuvant chemoradiation with both IMRT and 3D-CRT plans. Dosimetric parameters were calculated for the planned target volume (PTV) and organs at risk (OAR). Results: Both IMRT and 3D-CRT provided comparable PTV coverage. However, IMRT significantly improved kidney sparing, reducing the mean V20 value by 23% (p=0.01) for the right kidney and 26% (p=0.02) for the left kidney compared to 3D-CRT. IMRT also decreased the mean irradiated volume for both kidneys and the liver, as well as the V30 value for the liver, although these differences were not statistically significant. The dosimetric parameters for the spinal cord were comparable between IMRT and 3D-CRT plans. Conclusions: IMRT demonstrated better kidney sparing compared to 3D-CRT in adjuvant radiotherapy for gastric cancer, while PTV coverage was similar. Long-term follow-up is necessary to assess clinical outcomes and local recurrence rates for both treatment plans.